Radical scavenging activity of Chlorophytum borivilianum L. root extract and its protective role in cauda epididymal sperm integrity in Mus musculus after gamma irradiation - Vyas, Ruchi; Kesari, Kavindra Kumar; Lukac, Norbert; Slama, Petr; Roychoudhury, Shubhadeep; Sisodia, Rashmi (Frontiers in Cell and Developmental Biology, 2023)
Background:Chlorophytumborivilianum L. is a recognized herbal medicine for the management of impotency in South Asian countries. In Ayurveda, it is used for the management of multiple health conditions, including diabetes, infection, and cardiovascular diseases. Parts of the plant have been used as excellent antioxidants and scavengers of free radicals. Since oxidative stress plays an important role in spermatogenesis and fertility in male populations, this study evaluated the role of ethanolic extract of C. borivilianum roots in epididymal sperm maturation against adversities posed by ionizing gamma irradiation. Materials and methods: Antioxidant potential of C. borivilianum root extract (CRE) was evaluated through DPPH (2,2-diphenylpicrylhydrazyl) and NO (nitric oxide) scavenging assays. Four groups of healthy Swiss albino mice were constituted, which were labeled as follows: Group I: sham control, Group II: 7-day pre-treatment with 50 mg/kg CRE, Group III: 6 Gy irradiation without pre-treatment, and Group IV: 7-day pre-treatment with 50 mg/kg CRE and 6 Gy irradiation on day 7. Swiss albino mice were observed for 30 days and later sacrificed to evaluate sperm quality parameters. Results: CRE showed a remarkable antioxidant potential with IC50 values of 46.37 μg/ml and 98.39 μg/ml for DPPH and NO, respectively. A significant decline (p < 0.001) in cauda epididymal sperm count, motility, and viability was observed in Group III animals. Group IV also showed a substantial decline (p < 0.01) in all three parameters compared to Group I; nonetheless, these were significantly higher than Group III. Morphological alterations indicated a coiled and bent tail, with the presence of cytoplasmic droplets in Group III, which declined substantially in Group IV. The ultrastructure of sperm indicated higher curvature of hook in Group III than Group IV, indicating specific interferences in the sperm maturation process. Conclusion: It was concluded that pre-treatment with 50 mg/kg body weight of CRE could protect sperm during epididymal maturation against oxidative stress.